2003
DOI: 10.5194/angeo-21-1681-2003
|View full text |Cite
|
Sign up to set email alerts
|

Low- and high-frequency spectral behavior of cosmic-ray intensity for the period 1953–1996

Abstract: Abstract.A study of the cosmic-ray intensity power spectrum using the Climax Neutron Monitor data in the frequency range from 10 −9 Hz to 10 −7 Hz (which corresponds to periodicities from 11 years to a few months) during the period 1953-1996, was carried out by means of the successive approximations method of analysis and was compared against the power spectrum and the maximum entropy methods. The contributions of the time evolution of several peaks to the global one were obtained. Except for the well-known 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 38 publications
6
16
0
Order By: Relevance
“…6a show that the phase lag between SSN and CRI is large for odd solar cycles and negligible or even negative for even solar cycles. This result confirms results by previous authors (Nymmik and Suslov, 1995;Usoskin et al, 2001;Gupta et al, 2006;Mishra et al, 2006;and Mavromichalaki et al, 2007). Although a negative phase lag for solar cycle 20 (see Fig.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…6a show that the phase lag between SSN and CRI is large for odd solar cycles and negligible or even negative for even solar cycles. This result confirms results by previous authors (Nymmik and Suslov, 1995;Usoskin et al, 2001;Gupta et al, 2006;Mishra et al, 2006;and Mavromichalaki et al, 2007). Although a negative phase lag for solar cycle 20 (see Fig.…”
Section: Discussionsupporting
confidence: 83%
“…But since the Sun can influence the interplanetary space and the Earth, even by different mechanisms, the dominating frequencies observed in solar, interplanetary and Earth parameters can be very similar. For example, some periods in SA discussed by Hathaway (2010), and observed by Mavromichalaki et al (2003) and Kudela et al (2010) in CRI, are similar to the ones observed in LOD.…”
Section: T Barlyaeva Et Al: Rotation Of the Earth Solar Activity Asupporting
confidence: 62%
See 1 more Smart Citation
“…Results about quasi-periodicity ~150 days in CR measured on the ground can be found e.g. in papers (Mavromichalaki et al, 2003;Kudela et al, 2010).…”
Section: Periodic and Quasi-periodic Variationsmentioning
confidence: 95%
“…Figure 5 presents a brief summary of CR quasi-periodicities obtained in long time of measurements by NM. Figure 5 were reporteded by (Mavromichalaki et al, 2003) in the analysis of the data until 1996. For detailed analysis and for identification of contribution of various quasi-peridicities in the signal over the long time, the wavelet transform technique is suitable to be used in future, along with analysis of data from NMs at different geomagnetic cut-off positions and from muon telescopes sensitive to higher energies.…”
Section: Periodic and Quasi-periodic Variationsmentioning
confidence: 99%